The influence of jasmonic acid on the development of virus-free potato plants in vitro - Maja Ravnikar; Nada Gogala (Acta Biologica Slovenica, 1989)
The potato plant cv. Vesna tolerates PVM and is systemically infected with this virus. PYM was eliminated by tissue culture. The cultivation of healthy plants was unsuccessful if only the meri stem isolation was used, as virus particles were also found in the region of the meristems. But virus-free plants were obtained by the use of thermotherapy and/or the addition of jasmonic acid to the medium.